Increased Serum Levels of Cortisol and Inflammatory Cytokines in People With Depression. Issue 4 (April 2019) - Jia, Yong; Liu, Linlin; Sheng, Chuqiao; Cheng, Zhaohua; Cui, Lianzhi; Li, Min; Zhao, Yawei; Shi, Tongfei; Yau, Tung On; Li, Feng; Chen, Li
Abstract : Abstract: This cross-sectional study aimed at measuring the correlation and association between serum levels of cortisol, inflammatory cytokines, and depression and to measure the detection accuracy of serum levels of cortisol in serum samples. In total, 89 male participants were recruited into this study from June 15, 2017, to September 31, 2017. The Hamilton Depression Rating Scale, Beck Anxiety Inventory, and Pittsburgh Sleep Quality Index were used to investigate the mental health status of the participants. Serum concentrations of cortisol and inflammatory cytokines were determined. The serum cortisol concentration, anxiety level, and sleep quality were included in the final logistic regression model. Serum cortisol was able to accurately distinguish between patients with depression and those without depression. There was a significant positive correlation between serum cortisol levels and Hamilton Depression Rating Scale scores.